Fabrication and characterization of cefazolin-loaded nanofibrous mats for the recovery of post-surgical wound. (16th November 2016) - Rath, Goutam; Hussain, Taqadus; Chauhan, Gaurav; Garg, Tarun; Kumar Goyal, Amit
Abstract: The aim of the present study was to evaluate the wound healing performance of cefazolin-loaded gelatin nanofiber mats in post-operative wound. The obtained nanofibers were smooth, non-beaded and having diameter ranging from 620–680 nm. Nanofiber mats that are prepared exhibit high drug entrapment, excellent oxygen permeability and sustained drug release behavior. Further, medicated nanofiber mats showed an accelerated wound healing as compared to plain cefazolin. Macroscopical and histological evaluations demonstrated that cefazolin-loaded gelatin nanofiber showed increased epithelialization rate and collagen deposition. The results indicated that therapeutic strategies offer new prospects in the management of post-operative wound repair.